Investigating SFL-Based Genre Pedagogy and its Effect on EFL Learners’ Oral Reproduction of Stories - Sarmadi Kia, Farshid; Asadi, Nader; Zoghi, Masoud (KMAN Counseling & Psychology Nexus, 2023)
This study aimed to examine the effect of Systemic Functional Linguistics (SFL)-based genre instruction on the oral reproduction of short stories by Iranian EFL learners, focusing specifically on complexity and content transfer. The study employed a quasi-experimental pre-test/post-test design with 38 intermediate-level EFL learners (19 in the experimental group and 19 in the control group) from a language institute in Tabriz, Iran. Homogeneity was ensured using the Oxford Placement Test (OPT). The experimental group received genre-based instruction rooted in SFL principles, involving three instructional phases: deconstruction, joint construction, and independent construction of short stories. The control group followed conventional instructional methods. Two short stories were used for oral reproduction tasks at pre- and post-intervention stages. Complexity was assessed using Bygate’s (2001) framework of words per t-unit including content words (nouns, verbs, adjectives, adverbs), and content transfer was evaluated through a researcher-made checklist covering story events, sequence, and oral language. ANCOVA was applied to analyze differences between the groups while controlling for pre-test scores. The results revealed statistically significant differences in post-test performance between the experimental and control groups. In terms of complexity, ANCOVA showed that the experimental group significantly outperformed the control group (F(1,35) = 279.604, p < 0.001, partial η² = 0.889). Similarly, for content transfer, the experimental group achieved higher scores (F(1,35) = 218.470, p < 0.001, partial η² = 0.862). These results confirm the positive effect of SFL-based genre instruction on learners’ oral story reproduction. SFL-informed genre pedagogy significantly enhances both the linguistic complexity and content coherence of EFL learners’ oral performance, validating its implementation in language education to develop context-sensitive and functionally rich spoken discourse.